L’enseignement de la littératie numérique pour la formation à une citoyenneté numérique : une étude exploratoire - Jimmy Coste; Magali Brunel (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Digital technology and the place it occupies in our societies bring about changes and challenges that cannot be limited to a particular field, as they abound in different spheres, including education, which will be the subject of our reflections. The presence of digital technology in social exchanges and interactions highlights the need for specific skills to better master its various aspects. These skills are found in the concept of digital literacy. Based on the analysis of the first data from a qualitative study, we question the teaching of these digital literacy skills in the first degree in relation with digital citizenship training. In particular, we highlight the specific learning manifestations of this new object to be taught as well as specific teaching gestures.